Harnessing Game Theory for Strategic Chaos Engineering: A Pathway to Robust System Resilience - Reddy, Madhu Kumar (Global journal of Business and Integral Security, 2024)
In an era where complex systems are integral to organizational operations, the robustness of these systems against unexpected disruptions is a paramount concern. "Harnessing Game Theory for Strategic Chaos Engineering: A Pathway to Robust System Resilience" is a pioneering study that presents an integrated framework merging the predictive prowess of game theory with the dynamic testing mechanisms of chaos engineering. This research posits that by understanding the strategic interactions between system components through game-theoretic principles, particularly the Nash Equilibrium, one can anticipate and strengthen system responses to potential failures. The dissertation unfolds a novel Game Theory Framework for Strategic Chaos Engineering (GTF-SCE), which systematically identifies critical system components, maps their interactions, and applies game theory to design targeted chaos experiments. This methodology progresses from theoretical abstraction to empirical application, providing a strategic lens to chaos engineering practices. The dissertation evaluates the framework’s effectiveness through simulation and real-world case studies, analyzing data to refine resilience strategies continuously. This work contributes to the field of system resilience by offering a structured approach to preemptively recognizing and mitigating points of failure, thereby reducing downtime and operational losses. It is anticipated that the insights garnered from this research will not only advance academic discourse but also have significant implications for practitioners committed to enhancing the resilience of business systems.